Characterization of lysine acetylation in the peripheral subunit-binding domain of the E2 subunit of the pyruvate dehydrogenase-2-oxoglutarate dehydrogenase hybrid complex from Corynebacterium glutamicum. Issue 4 (22nd December 2020) - Komine-Abe, Ayano; Kondo, Naoko; Kubo, Shosei; Kawasaki, Hisashi; Nishiyama, Makoto; Kosono, Saori
ABSTRACT: In Corynebacterium glutamicum, pyruvate dehydrogenase (PDH) and 2-oxoglutarate dehydrogenase (ODH) form a unique hybrid complex in which Cg E1p and Cg E1o are associated with the Cg E2– Cg E3 subcomplex. We analyzed the role of a lysine acetylation site in the peripheral subunit-binding domain of Cg E2 in PDH and ODH functions. Acetylation-mimic substitution at Lys391 of Cg E2 severely reduced the interaction of Cg E2 with Cg E1p and Cg E3, but not with Cg E1o, indicating the critical role of this residue in the assembly of Cg E1p and Cg E3 into the complex. It also suggested that Lys391 acetylation inhibited the binding of Cg E1p and Cg E3 to Cg E2, thereby affecting PDH and ODH activities. Interestingly, the Cg E2-K391R variant strain showed increased l -glutamate production and reduced pyruvate accumulation. Kinetic analysis suggested that the increased affinity of the K391R variant toward pyruvate might be advantageous for l -glutamate production. Graphical Abstract: